Biodiversity Dynamics in a Ramsar Wetland: Assessing How Climate and Hydrology Shape the Distribution of Dominant Native and Alien Macrophytes - Fabio A. Labra; Eduardo Jaramillo (Plants)
Coastal wetlands provide critical ecological services but are threatened by the human, climatic, and hydrological changes impacting these ecosystems. Several key ecosystem services and functions rely on aquatic macrophyte plant species. We integrate 10 years of seasonal monitoring data (2014–2024) and climatic and hydrological datasets to assess how environmental variability influences two dominant aquatic macrophytes—the invasive and non-indigenous Elodea densa Planch. Casp. (Hydrocharitaceae) and the native Schoenoplectus californicus (C.A.Mey.) Soják—in Chile’s first Ramsar site, Carlos Anwandter, and a Nature Sanctuary. We modeled suitable habitat areas using MaxEnt software with Landsat 8 spectral bands and indices as predictive layers. We found significant recent decreases in temperature, river flow, and water level, with a nonsignificant shift in precipitation. We also observed marked spatial and temporal fluctuations in areas with suitable habitat areas for both macrophytes. Stepwise regression analyses indicated that Elodea densa expanded with increasing temperature over time but declined with water level variability. Schoenoplectus californicus showed contrasting effects, declining with rising temperature and water levels but expanding with higher precipitation. These findings emphasize the complexity of coastal wetland ecosystems under environmental stress and climate change and the need for further research for the conservation and management of coastal wetlands along migratory flyways such as the Southeastern Pacific Flyway.